Changing Nature of North-South Linkages : Stylized Facts and Explanations - Akin, Cigdem; Kose, Ayhan (Washington, D.C. : International Monetary Fund, 2007)
This paper examines the changing nature of growth spillovers between developed economies, the North, and developing countries, the South, driven by the process of globalization?the phenomenon of rising international trade and financial flows. We use a comprehensive database of macroeconomic and sectoral variables for 106 countries over the period 1960- 2005. We consider the South to be composed of two groups of countries, the Emerging South and the Developing South, based on the extent of their integration into the global economy. Using a panel regression framework, we find that the impact of the Northern economic activity on the Emerging South has declined during the globalization period (1986-2005). In contrast, the growth linkages between the North and Developing South have been rather stable over time. Our findings also suggest that the Northern and Emerging Southern economies have started to exhibit more intensive intra-group growth spillovers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet